Breves Notícias Sobre a Geologia dos Estados do Paraná e Santa Catarina - Maack Reinhard (Brazilian Archives of Biology and Technology, 2001)
The present short survey of the geology of the States of Paraná and Santa Catarina was written as a text to accompany sketches for the revision of the GEOLOGICAL MAP OF SOUTH AMERICA. It contains the results of geologic research up to the year 1947 in most concise form, without going into detail. As requested, the occurrence of useful minerals was not considered in the summary, and the list of bibliographical references has been condensed to the uttermost. Inasmuch as the author treated the Passa Dois Series in more detail, due to the reorganization of the Gondwana beds, the Archean and the Algonkian had to be reduced to the minimum. This was possible, since the innumerable details of the phenomena in the crystalline complex could not be represented in a geologic map of the given scale. The reorganization of the geologic constituents of Paraná and Santa Catarina is summarized in Stratigraphic Table nº 2, and is explained by the enclosed sketches.